The Holy Qur’ān as a Source for Al Sīrah al Nabawiyyah: An Analytical Study of the Selected Methodologies - Almhairi, Kaltham Omar Almajid (Journal of Islamic and Religious Studies, 2020)
This study dealt with the issue of the holy Quran source of the Prophet’s Biography, In order to identify the Quranic method in the biography, and the aspects that are concerned with clarifying its events, and its benefits and the consequent care of the interpreters to highlight the features of the biography using the method of interpretation and method and the extent of their use of the Quran in highlighting the feature of Prophet biography and events.